Optimizing Mental Health: The Impacts of Yoga Practices on Mental Health among Female College Student - V, Natesamurthy; Mohanakrishnan, R.; R, Ganesh; S, Thiruvangadam (Journal of Neonatal Surgery, 2025)
The purpose of this study was to determine how Asana and Meditational practices affected college women students' mental health. Twenty female students from SRM Institute of science and Technology, Kattankulathur, were selected at random as the study's subjects. They were between the ages of 19 and 22. The participants were split into two groups at random: group I practiced Asana and Meditation (n=10), while group II served as a control (n=10). For six weeks, members of Group I practiced Asana and Meditational practices on alternate days, attending one session per day. Group II took part in regular activities but did not receive any particular training. The data on a specific mental health criterion variable; The Warwick-Edinburgh Mental Wellbeing Scale was used to evaluate it. The dependent-t test and Analysis of Covariance (ANCOVA) were set at the 0.05 level of confidence for statistical analysis of the collected data. The statistical package SPSS- 22 version was used to analyze all of the data. It was determined that the group that combined Asana and Meditational practices had significantly better mental health than the control group, and the fact that the experimental and control groups differed significantly.